Two new canyon-dwelling frogs from the arid sandstone Isalo Massif, central-southern Madagascar (Mantellidae, Mantellinae) - Mercurio, Vincenzo; Andreone, Franco (Zootaxa, 2007)
We describe two new mantellid frogs of the subfamily Mantellinae from the arid sandstone Isalo Massif, central southern Madagascar. The first - assigned to the genus Gephyromantis, subgenus Phylacomantis - is a stream frog living in open canyons and associated gallery forest, and is phylogenetically related to G. corvus and G. pseudoasper. It has a larger maximum SVL than G. corvus (43 mm vs. 38 mm in the examined males) and is featured by a mostly contrasted and lighter dorsal pattern. Its advertisement call also differs from that of G. corvus in having more numerous and slightly longer notes per call composed of seven to ten sub-units, a clear harmonic structure, and a wider frequency spectrum with a higher dominant frequency. The second new species belongs to the genus Mantidactylus, subgenus Brygoomantis. It shares morphological and life history similarities with species of the subgenus Ochthomantis, in having comparatively expanded fingertips and leading a rupicolous and scansorial life.